Implementation of Profit Sharing Ratio for Barokah Agricultural Capital Products at BMT UGT Nusantara Capem Situbondo, East Java - Balqis Sriyandani (Journal of Islamic Economics and Finance, 2025)
This study aims to determine the transparency of the profit sharing ratio of Barokah Agricultural Capital by BMT UGT Sidogiri Capem Sempu because the ratio must be stated clearly so as not to cause uncertainty in the distribution and injustice of the amount of the ratio set. This type of research uses descriptive qualitative research with observation, interview, and documentation methods as data collection techniques. The results of the study are based on the results of interviews related to the application of the profit sharing ratio of the Barokah agricultural capital product, namely the determination of the profit sharing ratio on the Barokah agricultural capital product, the amount has been determined by BMT UGT Nusantara Capem Sempu, therefore when members have chosen a period to apply for a capital loan, BMT provides an offer only related to the borrower agreeing or disagreeing with the predetermined ratio. In the Barokah Agricultural Capital product at BMT Riyadhul Jannah, profit sharing has been implemented and implemented by Islamic law. Because BMT UGT Sidogiri Capem Sempu always implements Sharia principles in all its transactions.